Human Control Law and Brain Activity of Voluntary Motion by Utilizing a Balancing Task with an Inverted Pendulum. (7th July 2010) - Suzuki, Satoshi; Harashima, Fumio; Furuta, Katsuhisa
Abstract : Human characteristics concerning voluntary motion control are investigated, because this motion is fundamental for the machine operation and human-computer system. Using a force feedback haptic device and a balancing task of a virtual inverted pendulum, participants were trained in the task, and hand motion/force was measured, and brain activity was monitored. First, through brain analysis by near-infrared spectroscopy (NIRS) and motion analysis of the pendulum, we identified a participant who was the most expert. Next, control characteristics of the most expert were investigated by considering the operational force and delay factor of a human. As a result, it was found that predictive control based on velocity information was used predominantly although a perception feedback control against the pendulum posture worked. And it was shown that an on-off intermittency control, which was a strategy for the skilled balancing, can be described well by a liner model involving two types of time shifts for the position and velocity. In addition, it was confirmed that the cortex activity for observation in an ocular motor control area and visual processing area was strong to enhance above-mentioned control strategies.